Covid-19 Pandemic, What Is The Financial System Stability Policy In Indonesia? - Ashinta Sekar Bidari; Frans Simangunsong; Berlian Sesaria (CV. Inara, 2021)
This article aims to examine the preparedness and procedural policies of the Indonesian government in handling the impact of the Covid-19 pandemic on the banking sector. Where the current state of Indonesia is being hit by the Coronavirus outbreak which in terms of the economy has an impact, especially regarding Indonesia's economic growth. The policy issued by the Government is an anticipatory step to avoid an economic recession. In addition, the existence of system support and community behavior such as imposing a lockdownstaying and at home can reduce the spread of the epidemic to accelerate the process of economic recovery.